(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Jaipur, after its foundation, acquired the fame as one of the most graceful and planned cities - based on ’Grid-Iron Pattern’ of street planning of India, where it emerged as one of the major cities of Northern India during the l8th century. Though, the eighteenth century is generally considered as a period of stagnation and general decline in India, scholars are widely divided on its nature. A group of historians in their monumental works came out with their conclusion that there was a general decline in the 18th Century because of the decline of the Mughal Empire , though they have cited different causes of the decline of the Empire.